EVALUASI CACAT PENGERINGAN DAN PEMESINAN PADA EMPAT JENIS KAYU CEPAT TUMBUH TERMODIFIKASI PANAS - Ulfa Adzkia; Trisna priadi; Lina Karlinasari (Jurnal Penelitian Hasil Hutan, 2019)
Heat treatment is one method that can improve the quality of wood including for fast-growing wood species. However,this treatment can cause some drying defects as well as the change of machining properties after applying that heattreatment. The purpose of this study was to evaluate the effect of wood species and heating time on the drying andmachining defects. The fast-growing wood species used were teak, mangium, jabon, and sengon. The heat treatmentwas carried out at a temperature of 165°C with variation in time were 0 (control), 2, and 6 hours. The result showedthat the moisture content and wood density decreased after heat treatment. Heat treatment was succeeded to decrease themoisture content of 57% and caused a decreasing of density until 20% compared with control wood. The drying defectsof end checks in teak, mangium, jabon and sengon increased after 2 and 6-hour heat treatment. In the other hand, thesurface checks defect of teak, mangium, sengon and jabon were decreased. The defects after applying machining activitiesi.e. the defects of sanding, planing, shaping, and boring were decreased in teak, mangium, jabon and sengon after heattreatment of 2 and 6-hour. Jati was the best wood species in term of machining quality followed by jabon, mangium,and sengon after heat treatment. At the temperature of 165°C in 2 hours could be considered as the appropriate timefor heat treatment in term of obtaining minimal defects of drying and machining.